Pelatihan Pemanfaatan Game Edukasi Berbasis code.org Pada Pembelajaran di SDN Kedungdalem II - Faridahtul Jannah; Shofia Hattarina (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
Training on the Use of Code.org-based Educational Games in Delivering Material in Schools is a community service activity which aims to improve teachers' skills in using video-based learning media. This activity was carried out at SDN Kedungdalem II, attended by 12 teachers. This abstract explains the reasons for choosing this topic, namely to overcome challenges in delivering material in schools and utilizing the potential of technology in the learning process. The method used is interactive training and direct practice in creating and editing educational games for learning. During the training, teachers were provided with knowledge about code.org-based educational game concepts and technical skills to create interesting and effective educational games. The results of the training show an increase in teacher skills in using code.org-based educational games and more active student participation in learning. Teachers report increased student learning motivation and better understanding of concepts after implementing code.org-based educational games in the classroom. The conclusion from this activity is that this training succeeded in providing significant benefits for teachers and students. Using educational games based on code.org can improve the quality of learning and produce a more interactive learning environment